The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1590/s0301-80591998000400003
|View full text |Cite
|
Sign up to set email alerts
|

Biologia de Frankliniella schultzei (Trybom) (Thysanoptera: Thripidae) em tomateiro

Abstract: Frankliniella schultzei (Trybom) (Thysanoptera: Thripidae) foi encontrado infestando tomate (Lycopersicon esculentum Mill.) em Porto Alegre, RS. O estudo foi conduzido em laboratório, e os tripes acondicionados em potes de acetato, cobertos com parafilme e alimentados diariamente com folíolos de tomateiro. As observações do ciclo vital foram tomadas por duas gerações consecutivas (n = 109 indivíduos). O período embrionário demorou 4,3 d; o 1º ínstar 2,5 d; o 2º ínstar 2,5 d; a pré-pupa 1,2 d; a pupa 2,1 d; a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Leite et al (2002) reported that F. schultzei prefers to feed on the upper leaves to middle and lower leaves of tomato plants. Similarly, Pinent & Carvalho (1998) reported on studies where they fed F. schultzei on tomato leaflets to study its biology and life cycle. Surprisingly, we did not find F. schultzei feeding on tomato leaves during the past two years in Homestead.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leite et al (2002) reported that F. schultzei prefers to feed on the upper leaves to middle and lower leaves of tomato plants. Similarly, Pinent & Carvalho (1998) reported on studies where they fed F. schultzei on tomato leaflets to study its biology and life cycle. Surprisingly, we did not find F. schultzei feeding on tomato leaves during the past two years in Homestead.…”
Section: Resultsmentioning
confidence: 99%
“…The only morph found in Florida during this study period was the darker form, which is also a virulent strain between the two morphs, known to transmit at least four different plant viral diseases, including Tomato Spotted Wilt Virus (TSWV) (Sakimura, 1969), Tomato Chlorotic Spot Virus (TCSV), Groundnut Ring Spot Virus (GRSV) and Chrysanthemum Stem Necrosis Virus (CSNV) (Nagata & de Avila, 2000). While the majority of Frankliniella species are considered as anthophilous, F. schultzei have been observed feeding on both tomato and apple leaves (Jacobson, 1997; Pinent & Carvalho, 1998; Leite et al ., 2002) other than flowers of its host plant (Milne et al , 1996). The small size and thigmotactic behaviour is an advantage to thrips, helping them acquire the microhabitats in the field and escape from monitoring during initial stages of infestation.…”
Section: Introductionmentioning
confidence: 99%
“…However, these insects present a short life cycle, five to twelve days, with great potential for developing resistance to conventional insecticides 7,8 . Due to growing concerns about the environment and human health, to find methods to reduce the use of conventional synthetic insecticides is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…Because F. schultzei and M. persicae have short life cycles (PINENT; CARVALHO, 1998;CHAGAS FILHO et al, 2005), these insects have great potential to develop chemical resistance to insecticides. As a result of the emergence of resistant populations (FURIATTI;LAZZARI, 2003;LUOGEN et al, 2005;DOÐRAMACI;TINGEY, 2008), demand has increased for agricultural pest control methods that offer safety to humans, selectivity to natural enemies, biodegradability, economic viability and low environmental impact (VIEGAS, 2003).…”
mentioning
confidence: 99%